Hubungan Manajemen Konflik Keselamatan dan Kesehatan Kerja Serta Motivasi Kerja Terhadap Peningkatan Produktivitas Karyawan - Vinsensius Manuel Raka Wibisono; Taufiq Nur Muftiyanto; Primadia Putri Harmastuti (Maeswara : Jurnal Riset Ilmu Manajemen dan Kewirausahaan, 2025)
This study aims to determine the relationship between conflict management, occupational safety and health (OHS), and work motivation towards increasing employee productivity at PT. Ratna Beton Giriwoyo. The background of this study is based on the importance of human resource management as a company's main asset in achieving optimal productivity targets, especially in the construction industry sector which has its own challenges in creating a safe and productive work environment. This study uses a quantitative approach with data collection techniques through distributing questionnaires to all company employees as respondents. The data obtained are then analyzed statistically to determine the effect of each variable on employee work productivity. The results show that conflict management has a significant relationship with employee productivity. Properly managed conflict not only avoids a decline in performance but can also increase morale and cooperation between employees. In addition, the implementation of good occupational safety and health (OHS) contributes to a sense of security and comfort at work, thereby reducing workplace accidents and increasing employee focus and work efficiency. Work motivation has also been shown to have an important role in encouraging employees to achieve predetermined performance targets. These three variables, both partially and simultaneously, have a significant effect on employee work productivity. These findings suggest that an integrated approach to conflict management, OSH implementation, and increased work motivation can be an effective strategy for improving company performance. This research is expected to provide practical contributions to the management of PT. Ratna Beton Giriwoyo in formulating human resource development policies, as well as serve as an academic reference for researchers and students interested in human resource management, particularly in the construction sector.